Modifications of tau protein after cerebral ischemia and reperfusion in rats are similar to those occurring in Alzheimer's disease – Hyperphosphorylation and cleavage of 4- and 3-repeat tau. Issue 7 (July 2017) - Fujii, Hiroki; Takahashi, Tetsuya; Mukai, Tomoya; Tanaka, Shigeru; Hosomi, Naohisa; Maruyama, Hirofumi; Sakai, Norio; Matsumoto, Masayasu
Epidemiological studies have suggested a close relationship between cerebral ischemia and Alzheimer's disease (AD). To clarify the pathological association of tau dynamics in both diseases, we performed comprehensive studies on the posttranslational modification of tau in cerebral ischemia and reperfusion (I/R) in rats. The present study suggests that both 4-repeat and 3-repeat tau isoforms are hyperphosphorylated in cerebral I/R, similar to the case in AD. The generation of a 60-kDa Asp 421 -truncated tau in cerebral I/R preceded the emergence of a 17-kDa 3-repeat tau fragment and a 25-kDa 4-repeat tau fragment. The regional redistribution of tau from the neuropil to neuronal perikarya in our stroke model is thought to share similarity with that occurring in AD. In addition, immunofluorescence staining revealed the formation of axonal varicosities in cerebral I/R. Altered tau distribution may influence microtubule stability, disturbances in axonal transport, and the resulting formation of axonal varicosities. The staining profiles of granules in the ischemic cortex that were immunopositive for RD3, RD4, and AT8 in neuronal perikarya and that were argyrophilic on Gallyas-Braak staining were similar to those in AD. These findings suggest that transient cerebral ischemia shares a common pathology with AD, in the modification of tau protein.